دور الأحزاب السياسية في رسم السياسة العامة في الجزائر بين إشكالية الاستمرارية والمناسباتية - عثمان، صفاء Othman, Safa (جامعة محمد خيضر بسكرة - كلية الحقوق والعلوم السياسية - مخبر أثر الاجتهاد القضائي على حركة التشريع, 2023)
تمثل الأحزاب السياسية أحد التنظيمات النشطة في رسم السياسة العامة، إذ يعتبر داعما أساسيه لتكريس الديمقراطية في الأنظمة السياسية، باعتبار أن الأحزاب السياسية أحد القنوات التي تربط بين المواطن والحاكم بصفة مستمرة. لكن ما يشهده النظام السياسي الجزائري خاصة ركود هذه التنظيمات وتخليها عن دورها الأساسي لأسباب وعوائق تتنوع من مرحلة لأخرى، تختلف الإشكاليات التي تعيق دور الأحزاب في الجزائر بين عوائق إيديولوجية تتعلق بذهنية المجتمع الجزائري، كما نجد مجموعة من العوائق السياسية المتشابكة مثل موسمية ظهور الأحزاب السياسية في الحملات الانتخابية فقط، ومعاناتها من مشكلة الزعامة ونقص التداول السلمي على السلطة، في ظل وجود لنقص في الوعي وغياب الثقافة السياسية الإيجابية، كل هذه العوائق أدت بطريقة أو بأخرى إلى محدودية دور الأحزاب السياسية في رسم السياسة العامة في الجزائر. Representing political parties, one of the major particularly in public policy-making, where the political party is a key supporter of the consecration of democracy in political systems, But that seen in the Algerian political system, especially recession for these organizations and abandoning their essential role for reasons and obstacles. Different problems that hinder the role of political parties in Algeria between obstacles ideology related to the mentality of the Algerian society, We also find a group of intertwined political obstacles, such as the seasonality of the emergence of political parties in electoral campaigns only, and their suffering from a problem of leadership and the lack of a peaceful transfer of power, in the presence of a lack of awareness and lack of political culture positive, all these obstacles have led one way or another to the limited role of political parties in shaping public policy in Algeria.
Keywords: النظم السياسية -- الثقافة الانتخابية -- الأحزاب السياسية